Enzyme-assisted extraction, characterization, and in vitro antioxidant activity of polysaccharides from Potentilla anserina L. - Guo, Penghui; Chen, Hong; Ma, Jinpu; Zhang, Yuxuan; Chen, Hongfu; Wei, Ti; Gao, Dandan; Li, Jiansheng (Frontiers in Nutrition, 2023)
Introduction: Potentilla anserina (Potentilla anserina L.), also known as ginseng fruit, is a plant that can be used as both medicine and food. Potentilla anserina L. has high medical and nutritional value, such as strengthening the spleen and stomach, replenishing qi and blood, and astringing hemostasis. Methods: In this study, polysaccharides of potentilla anserina L. were extracted from the root using an enzyme-assisted extraction method. According to the principle of Box-Behnken design, response surface methodology was designed to optimize the extraction conditions. Fourier transform infrared spectroscopy and scanning electron microscopy were used to investigate the structure and appearance of potentilla anserina L. polysaccharides. The monosaccharide composition of potentilla anserina L. polysaccharides was determined by high performance liquid chromatography. The antioxidant activity was also studied. Results: Under the optimal extraction conditions (the ratio of solid to liquid, 1:15; ratio of cellulase to pectinase, 1:2; extraction pH, 8.0; enzyme reaction temperature, 60°C), the extraction yield of Potentilla anserina L. polysaccharides was 19.80±0.01%, equal to the model prediction value 19.84%. The data of fourier transform infrared spectrum, scanning electron microscopy, and high performance liquid chromatography showed the Potentilla anserina L. polysaccharide was a kind of α-pyran polysaccharide, mainly consisting of galactose, glucose, rhamnose, and arabinose. The antioxidant results showed that Potentilla anserina L. polysaccharides had a strong hydroxyl radical scavenging ability (IC50=0.367 mg/mL), superoxide anion scavenging ability (IC50=45.017 mg/mL), and a certain degree of total reducing ability. Discussion: Enzyme-assisted extraction is an efficient method to extract Potentilla anserina L. polysaccharides. The Potentilla anserina L. polysaccharides show a potential use in the functional foods as a natural antioxidant.